Reading engagement during the pandemic: The Case of Csu-Sanchez Mira (Cagayan, Philippines) students - Alegado, Rodel Francisco T. (Technium Social Sciences Journal, 2021)
With the sudden move away from school in many areas of the world, it is unclear if online education will persist post-pandemic, and how such a shift will impact the global education market. This study is aimed to discover the reading engagement of students during pandemic. The study made use of the descriptive research design using purposive sampling technique in order to determine the respondents of the study. A researcher made questionnaire was used as the main instrument. Result of the study revealed smartphone is the common gadget used by the students to access the internet. Most of them surf the net for 4-6 hours in order to acquire general knowledge found on social media. Online reading materials are read in different number of hours. English is the most preferred language. There is an underpinning reading engagement among the respondents. Moreover, it is also evident that made use of varied means to connect to the internet as they immersed themselves to online reading. Though it may sound the other way around, the students perceived that online reading is still a bearable experience. Thus, parents and other stakeholders should find ways to boost student reading engagement in order to maximize learning even in this time of pandemic.